Kinematics of the lower limbs in relation to rotational movement of the body in baseball batting: - Ae, K.; Koike, S.; Kawamura, T.; Nakajima, R. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The purpose of this study was to investigate the kinematic characteristics of the lower limbs in relation to the rotation movement of the body based on the moment of the ground reaction force. Twenty-two male collegiate baseball players (age: 19.8 ± 1.3 yr, height 1.75 ± 0.04 m, body mass 73.9 ± 6.2 kg, athletic career:12.1 ± 2.1 yr) participated. They performed baseball tee-batting, set at middle ball height for the strike zone. Threedimensional coordinate data were acquired with a motion capture system (Vicon-MX), and ground reaction force data for both legs were acquired with 3 force platforms. High and low groups (HG and LG) were categorized by the mean peak moment around the vertical axis of the body`s center of gravity caused by the ground reaction force. The period analyzed was that from stride-side foot contact with ground until ball impact, and 2 phases were defined as follows: backward phase, stride-side foot contact with ground until the peak moment of the ground reaction force; forward phase, the end of the backward phase until ball impact. Statistical analysis was conducted using an independent t-test between HG and LG (p <0.05), and the effect size was calculated (small: d = 0.2; middle: d = 0.5; high: d = 0.8). In the backward phase, the flexion angle of both hips was greater in the HG than in the LG at event1 (pivot-side: d = 0.74; stride-side: d =0.97). The abduction angle of the pivot-side hip was significantly greater in the HG than in the LG (stride-side foot contact with ground: d = 0.94; peak moment of the ground reaction force: d = 1.44). In the forward phase, the external rotation angle of the pivot-side hip was significantly greater in the HG than in the LG (d = 1.02), which contributed to the inter-group difference in the internal rotation angle at the instant of stride-side foot contact. These results indicate that the motions of both hip joints acted to rotate the whole body around the vertical axis effectively. The knowledge obtained from this study should provide useful suggestions and insights into coaching for movements of the lower limbs in order to improve batting performance in relation to the rotational movement of the body.